Automatic Hajj and Umrah Ritual Detection Using IMU Sensors - Khalil Chikhaoui; Mohammed Elrashidy; Motaz Alfarraj; Ali H. Muqaibel; Rida Sadagah; Abdullah Sharqawi (IEEE Access, 2022)
A smartphone can provide a wide range of practical applications and services thanks to its advanced sensing capabilities. However, the sector of Hajj and Umrah, which are rituals performed by millions of pilgrims, still lacks intelligent solutions that can improve the pilgrim experience using these sophisticated capabilities. This research aims to bridge this gap by introducing a solution that applies a real-time monitoring process to different Umrah activities (i.e., Tawaf and Sa’i) using smartphone sensors. In the proposed solution, the smartphone first tracks the pilgrim’s path with the help of inertial sensors, commonly known as the inertial measurement unit (IMU). Then, an algorithm is developed to detect and process the different activities performed by the user and provide helpful instructions accordingly for a comfortable and successful experience. The proposed system was tested and validated using real data for Tawaf and Sa’i activities. The extracted paths were compared with the GPS data for validation. Results showed that the paths were extracted effectively and the algorithm monitored both Tawaf and Sa’i successfully. The deviation between the real path and the extracted path using the proposed algorithm can be enhanced with proper GPS assessment and step-length calibration.